Association analysis identified superior haplotypes for improved salt stress tolerance in wheat (Triticum aestivum L.)Mendeley Data - Santosh Gudi; Harsimardeep S Gill; Serena Collins; Jatinder Singh; Devinder Sandhu; Sunish K Sehgal; Upinder Gill; Rajeev Gupta (Plant Stress, 2025)
Understanding genetic and molecular mechanisms regulating salt stress tolerance is crucial to develop salt resilient wheat cultivars. Here, we evaluated a genetically, phenotypically, and geographically diverse panel of 228 hexaploid spring wheat accessions, at US Salinity Laboratory, Riverside, CA, using greenhouse lysimeter system with two irrigation treatments: control (electrical conductivity of irrigation water as deci-Siemens per meter., (ECiw = 1.46 dSm-1) and saline (ECiw = 14 dSm-1). Salt stress had pronounced negative impact on several seedling traits, reducing shoot height (17.5 %), root length (15.5 %), tiller number (43.8 %), shoot weight (44.6 %), and root weight (35.8 %). However, salt stress increased root length-by-shoot height (3.75 %) and root weight-by-shoot weight (28.02 %) ratios, highlighting greater adverse effects on shoots compared to roots. Based on phenotypic variations, contrasting lines with hypersensitive or highly tolerant response to salt stress were identified. Notably, salt-tolerant lines were mainly landraces originating from seashores, ocean banks, or coastal marshes, whereas salt-sensitive lines were either landraces collected from freshwater-irrigated regions or modern breeding lines. Multi-locus genome-wide association studies (GWAS) and linkage disequilibrium (LD)-based grouping identified 25 high-confidence quantitative trait loci (QTLs). Candidate gene mining from flanking QTL regions and expression analysis revealed eight putative genes associated with salt stress tolerance. Haplotype analysis identified superior haplotypes of genes encoding sodium symporter (TraesCS1B02G413800) and peptide transporter (TraesCS5A02G004400). Superior haplotypes are mainly present in landraces but often lost in modern cultivars due to artificial selection pressure during breeding. In summary, this study identified salt tolerant genotypes and associated genomic regions, providing invaluable resources for breeding programs aimed at developing salt-resilient wheat varieties.